2021
DOI: 10.1002/ehf2.13304
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of plasma miR‐155 and miR‐206 as circulatory biomarkers in inflammatory cardiomyopathy

Abstract: Aims Establishing a diagnosis of inflammatory cardiomyopathy (iCMP) by non-invasive means remains challenging despite advances in cardiac magnetic resonance imaging. Previous studies suggested the involvement of microRNAs in the pathogenesis of iCMP. We examined the association of a predefined set of circulatory microRNAs with clinical characteristics of iCMP and evaluated their diagnostic performance in suspected iCMP. Methods and results Eighty-nine patients with clinical suspicion of iCMP were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…Evidence : MiR-155 level was measured in 13 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Its overexpression was found mainly in MCI (5 studies) [ 10 , 13 , 14 , 19 , 21 ] and InfDCM (3 studies) [ 12 , 18 , 20 ]. Only one study identified increased expression of miR-155 in ischemic cardiomyopathy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence : MiR-155 level was measured in 13 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Its overexpression was found mainly in MCI (5 studies) [ 10 , 13 , 14 , 19 , 21 ] and InfDCM (3 studies) [ 12 , 18 , 20 ]. Only one study identified increased expression of miR-155 in ischemic cardiomyopathy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study identified increased expression of miR-155 in ischemic cardiomyopathy [ 20 ]. The remaining studies did not detect increased miR-155 expression in other myocardial diseases (non-inflammatory DCM [ 11 , 12 , 17 , 18 , 19 ], rheumatic carditis [ 15 ], or hypertrophic cardiomyopathy [ 20 ]). Two studies performed ROC-AUC analysis, one for distinguishing between MCI and healthy subjects (AUC = 0.901) [ 13 ], and one for InfDCM and healthy subjects (AUC = 0.68) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This encapsulation prevents miRNA degradation, increasing their stability in the circulation, allowing miRNAs to have various paracrine effects [ 29 , 94 ]. Further, this stability also allows miRNAs to function as biomarkers for various conditions [ 50 , 95 , 96 ].…”
Section: Exosomesmentioning
confidence: 99%